1991
DOI: 10.1007/bf00235173
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sleep disturbances on subsequent physical performance

Abstract: The purpose of the study was to compare the cardiovascular, respiratory and metabolic responses to exercise of highly endurance trained subjects after 3 different nights i.e. a baseline night, a partial sleep deprivation of 3 h in the middle of the night and a 0.25-mg triazolam-induced sleep. Sleep-waking chronobiology and endurance performance capacity were taken into account in the choice of the subjects. Seven subjects exercised on a cycle ergometer for a 10-min warm-up, then for 20 min at a steady exercise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
2
5

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(51 citation statements)
references
References 29 publications
3
41
2
5
Order By: Relevance
“…Cardio-respiratory parameters measured during the steady state pre-load exercise were largely unaffected by the sleep deprivation. These findings are consistent with previous studies (Martin and Haney 1982;Martin 1981;Martin and Gaddis 1981;Mougin et al 1991) and therefore it can be suggested short-term sleep deprivation has little effect on cardio-respiratory function during sub-maximal exercise. Despite less total distance completed on the distance test following sleep deprivation participants perception of effort was similar.…”
Section: Discussionsupporting
confidence: 94%
“…Cardio-respiratory parameters measured during the steady state pre-load exercise were largely unaffected by the sleep deprivation. These findings are consistent with previous studies (Martin and Haney 1982;Martin 1981;Martin and Gaddis 1981;Mougin et al 1991) and therefore it can be suggested short-term sleep deprivation has little effect on cardio-respiratory function during sub-maximal exercise. Despite less total distance completed on the distance test following sleep deprivation participants perception of effort was similar.…”
Section: Discussionsupporting
confidence: 94%
“…Cognitive performance is negatively aVected by time-sincewaking and by sleep loss (Meney et al 1998;Van Dongen and Dinges 2005;Waterhouse et al 2001) and so sports performance with a substantial cognitive component will be more aVected by sleep loss than will performance when this component is smaller. Several studies (Bambaeichi et al 2005;Bullock et al 2007;Mougin et al 1991;Souissi et al 2003) indicate diVerences between types of sports performance in susceptibility to sleep loss, and loss of motivation subsequent to sleep loss has also been stressed (Blumert et al 2007). The recent reviews by Reilly and Edwards (2007) and by Samuels (2008) can be consulted for further details of this Weld.…”
Section: Summary Of Problems In Interpreting Rhythms Of Physical Perfmentioning
confidence: 97%
“…A maioria dos estudos que investigaram os efeitos da privação do sono no desempenho físico, focaram primariamente, seus efeitos no desempenho aeróbio submáximo (56)(57)(58)(59) e no consumo máximo de oxigênio (58,60,61) . Outras pesquisas examinaram as respostas neurológicas (62) e a força anaeróbia de indivíduos privados de sono (57,58,60) .…”
Section: Privação Do Sono E Exercício Físicounclassified
“…Mougin e colaboradores (61) (1991) notaram que, embora fosse possível sustentar a mesma intensidade máxima de exercício, os sujeitos que tiveram seu sono interrompido por um período de três horas exibiram um menor VO2 máx., uma alta ventilação máxima e submáxima, maiores valores da freqüência cardíaca e do lactato sanguíneo.…”
Section: Privação Do Sono E Exercício Físicounclassified